KAJIAN KEBERADAAN POS KESEHATAN DESA (PKD) TERHADAP PENCATATAN DAN PELAPORAN KEGIATAN POSYANDU DI DESA KEDUNGWULUH LOR KECAMATAN PATIKRAJA KABUPATEN BANYUMAS - Endo Dardjito; Dyah Umiyarni Purnamasari (Kesmas Indonesia, 2011)
ABSTRACT Basic Health Services in Banyumas have been conducted since 2005 with the midwifes as managing staff. The presence of PKD has caused several types of services, previously conducted in the community health center (puskesmas) to be moved to Village Health Posts (PKD). The mutation of some services from the community health center to PKD is considered to take effect on the recording and reporting activities which was previously done by the community health center. This study is a survey research which aimed to determine wether or not the presence of PKD affects the recording and reporting activities of the community health center. The study population were all the villages in Patikraja District which implements PKD. The samples were taken using the simple random sampling method. Data was collected from interviews and data archives of PKD activities. The results obtained showed that the coverage of MCH activities have reached target, except for exclusive breastfeeding (asi eksklusif) and baby visits, 65% of EFA/PUS joined family planning, immunization coverage has reached target, number of visits for basic medical services in PKD are as many as 2523 people, there are 1 mandiri and 4 purnama level posyandu with 28 active cadres, weighing coverage has not reached the D / S target (68%) and N / D (46%), there are 3 types of recording formats /registers in Posyandu. There is a need of simplification and reduction of some data in the format / register. Kata Kunci: PKD, recording, reporting Jurnal Kesmas indo. Volume 4(1) Januari 2011, hlm. 47-60